أثر آليات الحوكمة على أداء المصارف الإسلامية المدرجة في بورصة عمان: الدور الوسيط لحجم المصرف الإسلامي - محمد عمر محمود الذنيبات; Mohamaed Omar Mahmoud Althunibat (Universiti Sains Islam Malaysia, 2025)
Matric: 4191462 (FEM)